2023
DOI: 10.5114/jhk/169167
|View full text |Cite
|
Sign up to set email alerts
|

Plyometric Training Practices of Brazilian Olympic Sprint and Jump Coaches: Toward a Deeper Understanding of Their Choices and Insights

Abstract: Plyometric training is extensively used by coaches to enhance neuromuscular performance in a wide variety of sports. Due to the high demands of sprint speed and power output in elite sprinters and jumpers, sprint and jump coaches are likely to have great knowledge on this topic. Undoubtedly, this expertise is even more pronounced for Olympic coaches, who work with some of the fastest and most powerful athletes in the world, and who are required to continually maintain these athletes at optimal performance leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 117 publications
0
7
0
Order By: Relevance
“…Approximately 90% of these coaches have stated that “speed development” is the primary reason for prescribing plyometric exercises throughout the season ( Loturco et al, 2023b ). Given this crucial importance and confirmed effectiveness, along with the wide variety of plyometric exercises cited and utilized by these practitioners, we decided to conduct a specific study on this topic ( Loturco et al, 2023d ). From the results of this study, it was found that: 1) hurdle jumps, drop jumps, box jumps, assisted jumps, standing long jumps, bounding, and multiple hops, are the most popular exercises among these coaches.…”
Section: Speed Training Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 90% of these coaches have stated that “speed development” is the primary reason for prescribing plyometric exercises throughout the season ( Loturco et al, 2023b ). Given this crucial importance and confirmed effectiveness, along with the wide variety of plyometric exercises cited and utilized by these practitioners, we decided to conduct a specific study on this topic ( Loturco et al, 2023d ). From the results of this study, it was found that: 1) hurdle jumps, drop jumps, box jumps, assisted jumps, standing long jumps, bounding, and multiple hops, are the most popular exercises among these coaches.…”
Section: Speed Training Methodsmentioning
confidence: 99%
“…These exercises are prescribed for different purposes (i.e., developing acceleration, top-speed, and jumping qualities) during both preparatory and competitive periods; and 2) overall, plyometric training sessions are more frequently prescribed during the preparatory period than during the competitive period (2–3 vs. 1–2 times/week, respectively). For a more comprehensive understanding of this specific topic, readers are encouraged to refer to the first article of this collection ( Loturco et al, 2023d ), already published in the Journal of Human Kinetics .…”
Section: Speed Training Methodsmentioning
confidence: 99%
“…The best of three attempts measured to the nearest centimeter was recorded, with a two-minute rest period between jumps to ensure adequate recovery. Throughout all the jumps, players maintained their hands on their hips to eliminate the influence of arm swing impulse [30].…”
Section: Jump Assessmentsmentioning
confidence: 99%
“…[5][6][7] Therefore, examination of the training schemes and methods commonly employed by sprint coachesprofessionals who work with the world's fastest athletes-is of great interest for sport science research to further develop current practices. 8 In this regard, a series of recent survey studies have been conducted with the aim of describing and critically analyzing the training practices adopted by elite sprint coaches. [8][9][10] Additionally, it has been shown that sprint speed is a highly stable physical capacity, exhibiting minimal variations during the competitive season (ie, ±1.4% in 100-m sprint time over the annual training season) 11 and even throughout the professional careers of elite sprinters (ie, ≤0.2% during the 5 y preceding peak performance in the 100-m race time).…”
mentioning
confidence: 99%
“…8 In this regard, a series of recent survey studies have been conducted with the aim of describing and critically analyzing the training practices adopted by elite sprint coaches. [8][9][10] Additionally, it has been shown that sprint speed is a highly stable physical capacity, exhibiting minimal variations during the competitive season (ie, ±1.4% in 100-m sprint time over the annual training season) 11 and even throughout the professional careers of elite sprinters (ie, ≤0.2% during the 5 y preceding peak performance in the 100-m race time). 12 Hence, identifying effective strategies aiming to increase sprinting abilities (eg, acceleration and topspeed), and thereby producing a significant improvement in the competitive performance of sprinters, is of paramount importance for coaches and practitioners not only in track-and-field disciplines but also in a number of other sports.…”
mentioning
confidence: 99%